2018
DOI: 10.1016/j.ssresearch.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Offspring education and parental mortality: Evidence from South Asia

Abstract: Decades of research shows that education not only confers individual health benefits, but it also spills over to advantage subsequent generations. More recently, research has confirmed that the intergenerational health benefits of education can also flow upward: aging adults with more highly educated children enjoy better health and survival. Research has documented this finding in high-income settings, and also in select low- and middle-income contexts, raising questions about the mechanisms through which hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Zimmer et al (2002) found that, in Taiwan, the level of education of an adult child was positively associated with older parents’ greater physical functioning, and negatively associated with the mortality of their elderly parents, particularly among parents who already had severe health problems at the start of the mortality follow-up (Zimmer et al , 2007). While various later studies have also demonstrated an association between an individual's mortality and the quality of children in terms of their educational attainment, a growing share of this work has primarily focused on low- and middle-income countries (Zimmer et al , 2002, 2007; Yahirun et al , 2016, 2017; Yang et al , 2016; De Neve and Harling, 2017; Smith-Greenaway et al , 2018). As recently noted (De Neve and Kawachi, 2017), one reason for the dearth of research in high-income contexts may be the expectation that the influence of adult children on parental health is likely to be less pronounced in countries with developed welfare systems providing for the vulnerable and elderly.…”
Section: Education As a Family-level Resourcementioning
confidence: 99%
See 2 more Smart Citations
“…Zimmer et al (2002) found that, in Taiwan, the level of education of an adult child was positively associated with older parents’ greater physical functioning, and negatively associated with the mortality of their elderly parents, particularly among parents who already had severe health problems at the start of the mortality follow-up (Zimmer et al , 2007). While various later studies have also demonstrated an association between an individual's mortality and the quality of children in terms of their educational attainment, a growing share of this work has primarily focused on low- and middle-income countries (Zimmer et al , 2002, 2007; Yahirun et al , 2016, 2017; Yang et al , 2016; De Neve and Harling, 2017; Smith-Greenaway et al , 2018). As recently noted (De Neve and Kawachi, 2017), one reason for the dearth of research in high-income contexts may be the expectation that the influence of adult children on parental health is likely to be less pronounced in countries with developed welfare systems providing for the vulnerable and elderly.…”
Section: Education As a Family-level Resourcementioning
confidence: 99%
“…Such resources are associated with parents’ lower exposure to health risks ( e.g. smoking and alcohol use) and greater receipt of support (Smith-Greenaway et al , 2018), and are found to predict parents’ physical limitations (Zimmer et al , 2002; Yahirun et al , 2016). Although recent evidence also indicates that adult children's education is not necessarily associated with short-term changes in parents’ physical functioning in the Mexican context, it is nonetheless associated with increased parents’ longevity (Yahirun et al , 2017).…”
Section: Education As a Family-level Resourcementioning
confidence: 99%
See 1 more Smart Citation
“…Evidence on the health benefits of children's education for older generations dates back to at least the early 2000s (Zimmer et al 2002). Since then, a consistent positive association has been identified between children's education and a wide range of parental health outcomes, including: (1) parental mortality (Torssander 2013;Friedman and Mare 2014;Elo et al 2018;Smith-Greenaway et al 2018;Wolfe et al 2018;Sabater et al 2019); (2) parental physical health (Yahirun et al 2016(Yahirun et al , 2017Meyer et al 2019); and (3) parental mental health (Sabater and Graham 2016;Lee 2018;Peng et al 2019;Yahirun et al 2020). These associations persist after controlling for parents' demographic and socio-economic characteristics (De Neve and Kawachi 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These benefits vary by region and income. In low- and middle-income areas with inadequate public support and social security, such as in Tanzania, South Africa, and Nepal, the spillovers are even stronger [ 26 , 27 , 28 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%